Odpowiedzi

2010-03-10T21:33:48+01:00
2/5 (3-x)=-2 /*5/2
3-x=-5
-x=-5-3
-x=-8
x=8

2/4(2-3x)=-6 /*4/2
2-3x=-12
-3x=-12-2
-3x=-14
x=14/3
x=4 ⅔

0,6+x/2=x+1 /*2
1,2+x=2x+2
x-2x=2-1,2
-x=0,8
x=-0,8
2010-03-10T21:36:11+01:00
2/5 (3-x)=-2 /*5/2
3-x=-5
-x=-5-3
-x=-8
x=8

2/4(2-3x)=-6 /*4/2
2-3x=-12
-3x=-12-2
-3x=-14
x=14/3
x=4 ⅔

0,6+x/2=x+1 /*2
1,2+x=2x+2
x-2x=2-1,2
-x=0,8
x=-0,8
2010-03-10T21:39:13+01:00
6/5-2/5x=-2
-2/5x=-2-6/5
-2/5x=-4/5 /:(-2/5)
x=2


2/4(2-3x)=-6
1-6/4x=-6
-6/4x=-6-1
-6/4x=-7 /:(-6/4)
x=4 2/6


0,6+x/2=x+1
0,6+0,5x=x+1
0,5x-x=1-0,6
-0,5x=-0,4 /:(-0,5)
x=1,25